2001
DOI: 10.1002/ejsp.50
|View full text |Cite
|
Sign up to set email alerts
|

Psychological essentialism and the differential attribution of uniquely human emotions to ingroups and outgroups

Abstract: According to the psychological essentialism perspective, people tend to explain differences between groups by attributing them different essences. Given a pervasive ethnocentrism, this tendency implies that the human essence will be restricted to the ingroup whereas outgroups will receive a lesser degree of humanity. Therefore, it is argued that people attribute more uniquely human characteristics to the ingroup than to the outgroup. The present article focuses on secondary emotions that constitute such charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
594
2
54

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(695 citation statements)
references
References 39 publications
36
594
2
54
Order By: Relevance
“…Based on the classic paradigm of infra-humanization (Leyens et al, 2001), we experimentally manipulated the degree of humanity of the Turkish people. While control participants did not receive any information concerning Turkish emotional vocabulary, participants in the humanized condition learned from a scientific source that secondary emotions were used in Turkey more than primary ones and to the same extent than European countries.…”
Section: Studymentioning
confidence: 99%
“…Based on the classic paradigm of infra-humanization (Leyens et al, 2001), we experimentally manipulated the degree of humanity of the Turkish people. While control participants did not receive any information concerning Turkish emotional vocabulary, participants in the humanized condition learned from a scientific source that secondary emotions were used in Turkey more than primary ones and to the same extent than European countries.…”
Section: Studymentioning
confidence: 99%
“…As social control is considered effective when it elicits functional reactions of reparation and conformity (i.e., moral emotions), people tend to intervene when they believe that others will experience these specific emotions. As mentioned earlier, this anticipation of an in-group members' moral emotions might also reflect the infrahumanization bias, according to which people consider members of their in-group as more essentially human than members of out-groups (Leyens et al, 2000(Leyens et al, , 2001(Leyens et al, , 2003. One can imagine that manipulating groups that are more socially relevant or that differ on important social variable such as ethnicity or power would produce even greater asymmetrical attribution of moral emotions to the deviant.…”
Section: Discussionmentioning
confidence: 97%
“…generosity, charity, reliability, helpfulness) than higher status groups (Piff, Kraus, Cote, Cheng, & Keltner, 2010). Research determined that participants have less dehumanization attitude toward correspondents from the same socio-economic status than they have toward those from different statuses (Leyens et al, 2001). Another study revealed that those from higher status groups have dehumanizing attitudes toward those from lower status; however, those from lower status groups do not share this attitude toward those from higher status groups (Capozza et al, 2012).…”
Section: High Statusmentioning
confidence: 98%